Attitude of Student-teachers towards the Humanistic Approach to Teaching and Learning in School - Roma Kumar, (JOURNAL OF INDIAN EDUCATION, 2019)
The purpose of the present work was to study the attitude of the student-teachers of three Teacher Training Institutes of Delhi, towards the Humanistic Approach to teaching and learning in schools. The sample consisted of 200 respondents studying in these institutes. The questionnaire, which is a Likert five-point scale, developed by Kyriacou and Cheng (1993), was used as a research tool to collect quantitative data for the study and Structured Respondent Interviews of ten students-teachers were used as the qualitative component of methodology to supplement the data derived from the responses to questionnaires. Further, differences in the attitude of the respondents with respect to their institutes, gender and subject stream were also found. The t-test, at 0.10 level, was used to find the significance of the differences obtained from quantitative analysis. The major finding was that the attitude of the total sample was ‘strongly humanistic towards teaching and learning in schools. It was found the female student teachers of the sample had more humanistic attitude towards teaching and learning than the male student teachers. The respondents’ interviews reflected that most of the characteristics of the teachers, whom the sample interviewees liked in their school time, were in coherence with the characteristics of a humanist teacher, i.e., caring, approachable, sympathetic, and tolerant towards the interpretations of the students, and also, keeping relations beyond the classroom with the students.